Assessment of Married Men Involvement in Family Planning Practices: A Qualitative Study of Akure South Local Government Area of Ondo State, Nigeria (American Journal of Physical Education and Health Science, 2024)
The non-accommodation of men in the family planning programs has been identified as one of the contributory factors for the low utilization of FP methods in this male-dominated society like Nigeria. Male involvement can lead to uptake in acceptance and prevalence rate of family planning methods and practices in Nigeria.This paper aimed to study the involvement of married men in the family planning practices in Akure South Local Government Area of Ondo State, Southwestern Nigeria. The primary data were collected from 250 married informants who satisfied the eligibility criteria and were assessed througha self-administered questionnaire and selected from the sample population across 11 political wards in the Akure South Local government area using a multi-stage random sampling technique. The secondary data were generated from government publications, journals, newspapers, and relevant internet materials. The presentation and analyses of data were done using descriptive statistics (frequency table, percentage and numbers). The study’s findings revealed that married men’s knowledge about family planning practices is high while exhibiting low involvement in FP and low utilization of the FP methods. However, the number of children, socio-cultural beliefs, financial status, education and religion are discovered to be among conditional factors that influence contraceptive use among married partners. The study therefore recommended increased health promotion and education of family planningprogrammes among the residents and involvement of men as a target in all FP programmes and introduction of family planning services in National Health Insurance Scheme in order to reduce associated misconceptions about contraceptives methods and increase the usage.